The Influence of Entrepreneurial Education and Entrepreneurial Motivation on The Entrepreneurial Interest of Fkip Economics Education Students of Lambung Mangkurat University - Nafarin, Muhammad Alwan; Hasanah, Mahmudah; Setiawan, Ananda; Nor, Baseran (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to determine the influence of entrepreneurial education and entrepreneurial motivation on the entrepreneurial interest of FKIP Economics Education students, Lambung Mangkurat University. This study uses a quantitative approach with the type of associative research. The population in this study amounted to 155 students who had completed entrepreneurship courses, while the data analyzed came from 152 respondents. Data collection was carried out through a questionnaire with a Likert scale and analyzed using multiple linear regression. Hypothesis testing was carried out through the t-test and the F-test. The results showed that entrepreneurial education had a positive and significant effect on students' entrepreneurial interest with a t-value of 4.077 and a significance of <0.001. These results show that entrepreneurship education and motivation have a role in increasing students' interest in entrepreneurship.